The Cytoskeleton in Health and Disease - Schatten, Heide (Springer New York : Imprint: Springer, 2015)
This volume explores the cytoskeleton, examining its structural and functional roles and its dysfunctions which often lead to disease. Microtubules, microfilaments, intermediate filaments, and cytoskeletal functions and dysfunctions in different organ systems are thoroughly discussed. The text is organized into four sections, each of which covers specific subtopics. These consist of an introductory chapter followed by topics of current interest and expert-provided contributions which include each topic's key cell and molecular details. Comprehensive yet concise,  The Cytoskeleton in Health and Disease presents cutting- edge new knowledge balanced with background information, both of which are readily understandable for the newcomer and for the experienced researcher alike. The book highlights the new aspects of the research and its impact on  the design of new strategies or the identification of new targets for therapeutic intervention. This book will be essential reading for scientists, students, teachers who are interested in expanding their knowledge related to the cytoskeleton for diagnostic, therapeutic or research-based purposes.